2012
DOI: 10.1002/ijc.27816
|View full text |Cite
|
Sign up to set email alerts
|

Lung carcinogenesis by tobacco smoke

Abstract: Cigarette smoke is a complex mixture of chemicals including multiple genotoxic lung carcinogens. The classic mechanisms of carcinogen metabolic activation to DNA adducts, leading to miscoding and mutations in critical growth control genes, applies to this mixture but some aspects are difficult to establish because of the complexity of the exposure. This paper discusses certain features of this mechanism including the role of nicotine and its receptors; lung carcinogens, co-carcinogens and related substances in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
308
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(320 citation statements)
references
References 82 publications
(207 reference statements)
4
308
0
8
Order By: Relevance
“…Cigarette smoke remains to be a major etiological risk factor for lung cancer (1,4); a previous study reported that an increase in the incidence of LAC was correlated with cigarette smoking (5). In addition, several signaling pathway abnormalities in lung cancer have been found to be associated with smoking (6,7). Therefore, further studies that aim to identify the signals activated by smoking-associated carcinogens may aid in the development of targeted therapies for lung cancer patients with a history of smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoke remains to be a major etiological risk factor for lung cancer (1,4); a previous study reported that an increase in the incidence of LAC was correlated with cigarette smoking (5). In addition, several signaling pathway abnormalities in lung cancer have been found to be associated with smoking (6,7). Therefore, further studies that aim to identify the signals activated by smoking-associated carcinogens may aid in the development of targeted therapies for lung cancer patients with a history of smoking.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The carcinogenesis for lung cancer by tobacco smoke derived significant attentions on B[a]P and NNK in lung cancer development and progression, inducing the mutations of Ras genes or P53 via different signal pathways. 12,13 For example, NNK-induced Kras mutation from…”
Section: Introductionmentioning
confidence: 99%
“…Also found that cigarette smoking was the chief cause of death after notifying the symptoms of respiratory diseases, Trachea bronchus, pulmonary emphysema, oropharynx, and renal pelvis and for adenocarcinoma of the esophagus in smokers 16 .Smoke from cigarette contain plenty of carcinogenic chemicals, such as nicotine, CO, PAH and NNitrosamine etc. 17 .Principally, fifty five carcinogenic compounds, including amines, aldehydes, inorganic and organic compounds in smoke have tendency to nick bio molecules and DNA and may cause disorder in gene expression and cancer too 18 .The uncontrolled cell growth in lung tissues kills lung patients and pose a challenge for efforts to extend and improve the lives of these patients. The amount of functioning on all aspect of p53, reflects a key role in early event of lung carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%